Coñecemento do galego no acceso á función pública local un estudo de caso: Moaña - Ríos Santomë, Soledad (Madrygal. Revista de Estudios Gallegos, 2005)
The aim of this article is to assess the knowleedge of Galician language in the selective process whic take place in the Local Administration, specifically in the Council of Moaña, during the last twenty years (1980-2000). Despite the fact that it is a subject which has ben continuosly legislated since 1983, date of the Linguistics Normalization Law, the regulation was not always respected.